The Role of Psychological Capital on Work Readiness Among Final-Year University Students - A. M. Farhan Rifqi; Lukman; Andi Nasrawati Hamid (Universitas Ahmad Dahlan, 2026)
This cross-sectional study examined psychological capital's influence on work readiness among 403 final-year Indonesian undergraduate students actively completing theses. Validated Psychological Capital Questionnaire (17 items, α=0.850) and Work Readiness Scale (32 items, α=0.926) measured continuous predictor and outcome variables. Simple linear regression revealed psychological capital's exceptionally strong effect (β=0.891, R²=0.797, p<0.001), explaining 79.7% work readiness variance. Multiple regression confirmed all dimensions significantly contributed, with resilience strongest (β=0.420). Moderate levels predominated (psychological capital 68.73%, work readiness 51.86%), establishing resilience training priority for thesis supervision and pre-graduation career preparation. Cross-sectional self-report design limits causality; longitudinal employer-rated validation recommended.